2012
DOI: 10.1073/pnas.1200642109
|View full text |Cite|
|
Sign up to set email alerts
|

Solute carrier family 3 member 2 (Slc3a2) controls yolk syncytial layer (YSL) formation by regulating microtubule networks in the zebrafish embryo

Abstract: The yolk syncytial layer (YSL) in the zebrafish embryo is a multinucleated syncytium essential for embryo development, but the molecular mechanisms underlying YSL formation remain largely unknown. Here we show that zebrafish solute carrier family 3 member 2 (Slc3a2) is expressed specifically in the YSL and that slc3a2 knockdown causes severe YSL defects including clustering of the yolk syncytial nuclei and enhanced cell fusion, accompanied by disruption of microtubule networks. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 46 publications
(66 reference statements)
1
39
0
Order By: Relevance
“…The following expression constructs were used: membrane-GFP (mem-GFP) (Kimmel and Meyer, 2010), membrane-RFP (mem-RFP) (Iioka et al., 2004), H2B-EGFP (Keller et al., 2008), H2A-mCherry (Arboleda-Estudillo et al., 2010), RhoA (Takesono et al., 2012), and N-terminal fragment of Mypt1 (Jayashankar et al., 2013). mRNA was synthesized using mMESSAGE mMACHINE SP6 kit (Ambion).…”
Section: Methodsmentioning
confidence: 99%
“…The following expression constructs were used: membrane-GFP (mem-GFP) (Kimmel and Meyer, 2010), membrane-RFP (mem-RFP) (Iioka et al., 2004), H2B-EGFP (Keller et al., 2008), H2A-mCherry (Arboleda-Estudillo et al., 2010), RhoA (Takesono et al., 2012), and N-terminal fragment of Mypt1 (Jayashankar et al., 2013). mRNA was synthesized using mMESSAGE mMACHINE SP6 kit (Ambion).…”
Section: Methodsmentioning
confidence: 99%
“…Epiboly movements, yolk syncytial layer formation and axonal transport are all processes that require an intact microtubule cytoskeleton (Du et al, 2012;Guzik and Goldstein, 2004;Hsu et al, 2006;Lachnit et al, 2008;Solnica-Krezel and Driever, 1994;Strahle and Jesuthasan, 1993;Takesono et al, 2012). Parallel microtubule arrays in early zebrafish embryos were first described by Jesuthasan and Strahle (Jesuthasan and Strahle, 1997), by Tubulin immunostaining in fixed embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Since Rock is inactivated directly by Gem (Ward et al, 2002) and indirectly by Rho-GAP (Riento and Ridley, 2003), they are potential targets for this maternal signal. Another possible model of YSL formation was recently proposed by Takesono and colleagues, in which solute carrier family 3 member 2 (Slc3a2) inhibits RhoA/Rock signalling via c-Src activation, thereby regulating microtubule dynamics and YSL organization (Takesono et al, 2012). They reported that Slc3a2 knockdown caused YSL expansion, which was rescued by treatment with Y27632.…”
Section: Resultsmentioning
confidence: 99%
“…Rho kinases (Rocks) are downstream effectors of Rho signalling – activated GTP-bound Rho binds to Rock at its Rho-binding domain, thereby relieving the autoinhibitory loop formed by interaction between the N- and C-termini of Rock (Riento and Ridley, 2003). Although the molecular mechanism underlying cytokinesis has been a matter of intense investigation, the molecular mechanism underlying YSL formation is only just beginning to be elucidated (Takesono et al, 2012). This report demonstrated that solute carrier family 3 member 2 (Slc3a2) inhibits the RhoA/Rock pathway via phosphorylation of c-Src to modulate YSL microtubule dynamics and YSL formation.…”
Section: Introductionmentioning
confidence: 99%